2021
DOI: 10.1007/s42832-021-0085-3
|View full text |Cite
|
Sign up to set email alerts
|

Considerable impacts of litter inputs on soil nematode community composition in a young Acacia crassicapa plantation

Abstract: Aboveground litter inputs and root exudates provide basal resources for soil communities, however, their relative contributions to soil food web are still not well understood. Here, we conducted a field manipulative experiment to differentiate the effects of litter inputs and living root on nematode community composition of surface and subsoils in a young Acacia crassicapa plantation in southern China. Our results showed that both litter addition and root presence significantly enhanced soil nematode abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The presence of Acacia crassicapa Cunn. ex Benth leaf litter altered trophic composition of nematodes and increased the ratio of predators by 123.9% when compared to uncovered plots [41].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The presence of Acacia crassicapa Cunn. ex Benth leaf litter altered trophic composition of nematodes and increased the ratio of predators by 123.9% when compared to uncovered plots [41].…”
Section: Discussionmentioning
confidence: 95%
“…Under shredded paper (alone or combined either with biosolids or with MGW compost), the abundance of omnivorous and predatory nematodes (Aporcelaimellus Heyns, Carcharolaimus Thorne, Clarkus Jairajpuri, 1970 Discolaimus Cobb, Paraxonchium Krall, Sectonema Thorne, and Seinura Fuchs) was higher than under the unmulched control, alfalfa (Medicago sativa L.) hay or plastic mulch in apple (Malus domestica Horkh) [39]. Mulching may be a cornerstone to enhance populations of predatory nematodes in open fields [40], and a recent survey [41] investigating the effect of surface leaf litter found that not only the abundance of nematodes increased, but their trophic composition has also changed in favor of bacterivore and omnivore-predatory taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Plant bodies contain various amounts of cellulose, chitin, flavonoids, lignin, phenols, ricin, saponins, tannin, terpenoids, etc., which significantly affect the growth of microorganisms and thus affect the resulting cooperating soil microbiome during the decomposition. The addition of compost was shown to increase the overall nematode presence, while modifying species composition, favouring bacterivorous taxa and decreasing the ratio of fungivorous nematodes [201].…”
Section: The Impact Of Mgwc On Microbial Lifementioning
confidence: 97%